2015 IEEE 15th International Conference on Nanotechnology (IEEE-NANO) 2015
DOI: 10.1109/nano.2015.7388733
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanowire-FET for charge-based sensing of protein biomolecules

Abstract: -Top-down method was used oxide (ZnO) nanowire field effect tran biosensor. The nanosensor was used to meas characteristics of lysozyme (LYSO) and bovin (BSA) protein solutions in phosphate buffe The LYSO and BSA proteins are oppos measurement pH of 7.4. Subthreshold voltag and 700 mV due to surface charge effect on t is obtained for the LYSO and BSA solution NWFET sensitivity of 72 % is achieved for th while the BSA proteins resulted in a sensitivity Keywords-zinc oxide, field effect tran device, nanosensor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 15 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…Assumption (a) has been widely experimentally evidenced for biosensing and pH sensing. 30,35,70,119,180 Assumption (b) has been shown to be approximately the case for pH sensing and assuming a consistent oxide material between devices. 181,182 As a result of this, pH sensing FET Sensitivity can be predicted via eqn (9) prior to pH sensing experiments simply by measuring the subthreshold slope and using knowledge of the oxide material.…”
Section: Data Analysis Of Responses In Streptavidin and Ph Sensingmentioning
confidence: 99%
“…Assumption (a) has been widely experimentally evidenced for biosensing and pH sensing. 30,35,70,119,180 Assumption (b) has been shown to be approximately the case for pH sensing and assuming a consistent oxide material between devices. 181,182 As a result of this, pH sensing FET Sensitivity can be predicted via eqn (9) prior to pH sensing experiments simply by measuring the subthreshold slope and using knowledge of the oxide material.…”
Section: Data Analysis Of Responses In Streptavidin and Ph Sensingmentioning
confidence: 99%
“…Four different environments were measured: AIR, PBS, lysozyme from chicken white (LYSO: Fluka 62970), bovine serum albumin (BSA: Sigma A3059) [5]. Measurements were carried out in air, then in liquid and then in air again.…”
Section: Procedures For Protein Sensingmentioning
confidence: 99%
“…The mechanism of the protein adsorption on the Al 2 O 3 surface is in equilibrium with the protein concentration in solution. Table 1: Experimental procedure that describes the sequence of measuring the low doped biosensor for four different environments (AIR, PBS, lysozyme from chicken white (LYSO: Fluka 62970), bovine serum albumin (BSA: Sigma A3059)) [5].…”
Section: Procedures For Protein Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the NWFET channel length, width and thickness can be varied to meet a range of performance specifications [18]. Recent studies on this fabrication approach have shown good transistor performance and also demonstrated biosensor functionality [19], [20]. Further improvement on the NWFET characteristics has been achieved by reducing the nanowire surface roughness, which is known to have a significant effect on the electrical properties of nanowires [21], [22].…”
Section: Introductionmentioning
confidence: 99%